Effects of prebiotic, probiotic and synbiotic on performance, cecal microbial diversity and yolk cholesterol content of laying hens - Tang, Shirley Gee Hoon; Sieo, Chin Chin; Ramasamy, Kalavathy; Saad, Wan Zuhainis; Wong, Hee Kum; Ho, Yin Wan (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
This study investigated the effects of prebiotic, probiotic and synbiotic on the performance, cecal microbial diversity and yolk cholesterol content of laying hens. One hundred and sixty Hisex Brown hens, aged 20 weeks of age, were randomly allotted to four diets: basal diet (control), basal diet + 1% prebiotic isomaltooligosaccharide (IMO) (prebiotic diet), basal diet + 0.1% probiotic PrimaLac® (probiotic diet), and basal diet + 1% IMO + 0.1% PrimaLac® (synbiotic diet). Cecal microbial populations and community of hens were assessed by 16S rRNA gene sequencing and quantitative real-time PCR (qPCR) methods, respectively, at 36 weeks of age. Cholesterol content of egg yolk was analyzed by gas chromatography at 24, 28, 32 and 36 weeks of age. The results showed that the body weight gain, feed intake, feed conversion ratio (FCR), egg production, egg weight and egg mass were significantly (P<0.05) improved in hens fed prebiotic, probiotic or synbiotic diet from 20-36 weeks of age. Sequencing results revealed that the prebiotic, probiotic or synbiotic feeding increased the abundance of Lactobacillusand decreased the abundance of Enterobacteriaceae. The abundance of Bifidobacterium was increased in prebiotic- or synbiotic-supplemented hens. At 36 weeks of age, qPCR results showed that prebiotic, probiotic or synbiotic feeding significantly (P<0.05) increased the populations of Lactobacillus and Bifidobacterium, but decreased the populations of Enterobacteriaceae and Escherichia coli. Supplementation of prebiotic, probiotic or synbiotic had significantly (P<0.05) lowered the yolk cholesterol content of laying hens at 24 and 28 weeks of age, but not at 32 and 36 weeks of age. The results of the study indicate that prebiotic, probiotic or synbiotic supplementation had similar positive effects on the performance, cecal microbial diversity and cholesterol content of egg yolk in laying hens at 20-36 weeks of age.